Development and recovery: the realities of the new inter dependence: report by the Secretary-General of the Sixth Session of the Conference (United Nations New YorkUS, 1984)
Suggests that the revival of the world economy requires both a sustained upturn of the economies of the industrialized countries and the reactivation of development. Proposes as an immediate response, a programme of recovery. Looks at the dynamics of the new interdependence in the longer term perspectives. Indicates that the systems that underpin international economic realtions should be supportive of the efforts of the developed market - economy countries to achieve better macro-economic management and structural adjustment. They should be supportive of the development process in the developing countries, and the efforts of these countries to carry out corrections and adjustments in their economies.
DC